Creative development of preschool children by means of manual work: psychological-pedagogical aspect of future teacher's training - Galina Boryn (Vasyl Stefanyk Precarpathian National University, 2017)
Psychological-pedagogical aspect of future teacher's training to creative development of preschool children by means of manual work in the conditions of higher educational institution is analyzed the article. The main focus is on the fact that the decisive factor in this process is the teacher's personality, his ability to organize this activity properly and to implement appropriate pedagogical support. Key words: creative development, children of preschool age, manual work, educational environment